Famous physicians from Messina - Giuseppe Magazzù (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche)
The aims of this article are i) to present the characteristics of famous, historical people in the field of Medicine who followed one another at the University of Messina; ii) identification of their peculiarities which allowed them to make scientific discoveries which have remained in the history of Medicine and Science; iii) reflection on the ability of some people to grasp aspects other than merely scientific ones from observation.